New advances in process integration research - Abdul Manan, Zainuddin (2004)
This paper highlights some of the key recent advances in research related to Pinch Analysis, particularly those developed in the Department of Chemical Engineering, Universiti Teknologi Malaysia. The focus is on the development of systematic conceptual and heuristic design and retrofit techniques for efficient heat, mass and water recovery even though many recent work in the area has also concentrated on the use of mathematical programming.